(untitled) (Research, Society and Development, 2022)
Studies about the evaluation of learning have contemplated several aspects and factors that affect the evaluation practices of teachers. In this sense, the objective of this research is to investigate the evaluative practices of literacy teachers working in 2nd year classes at a municipal school in Horizonte - Ceará. The work was based on a qualitative investigation with the following methodological procedures for data collection: documentary research and semi-structured interview. With regard to the theoretical-conceptual study, issues related to literacy are addressed Morais (2006), Soares (2013); learning assessment; Luckesi(2011), Vasconcelos( 2006), Hoffmann (2000), Hadji ( 2001) and to evaluative practices, Luckesi (2005), Hoffmann(2005) and Esteban (2002). In short, from the analysis of the data, it was observed that the teachers perceive the evaluation of learning as a permanent practice in the teaching and learning process and report making use of the results in the formative perspective, using different evaluative instruments such as a diagnostic test of reading and writing, portfolios, readings, works with orality among others and didactic-pedagogical approaches. It is also emphasized the importance of expanding the theme of evaluation in continuing education for teachers, in the sense of re-signifying their practices, as well as reflecting on the forms of evaluation, specifically in literacy.